Radiological and Histopathological Evaluation in Reduction Mammoplasty (Annals of Medical Research, 2021)
Aim: Mammography and ultrasonography are helpful diagnostic methods for the detection of asymptomatic lesions prior to reduction mammoplasty operations. Preoperative radiological evaluation does not give accurate results all time. Consequently, preoperative radilological and postoperative histopathologic evaluation were used together in order to diagnose the premalignant and silent cancer foci.
Keywords: s: Reduction Mammoplasty; Histopatholgic Evaluation; Ultrasonography; Mammography.